2019
DOI: 10.3354/dao03382
|View full text |Cite
|
Sign up to set email alerts
|

Eelgrass pathogen Labyrinthula zosterae synthesizes essential fatty acids

Abstract: Negative consequences of parasites and disease on hosts are usually better understood than their multifaceted ecosystem effects. The pathogen Labyrinthula zosterae (Lz) causes eelgrass wasting disease but has relatives that produce large quantities of nutritionally valuable long-chain polyunsaturated fatty acids (LCPUFA) such as docosahexaenoic acid (DHA). Here we quantify the fatty acids (FA) of Lz cultured on artificial media, eelgrass-based media, and eelgrass segments to investigate whether Lz may similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Positive amplification of L. zosterae DNA from diseased tissue samples confirmed the presence of this pathogen in lesion tissue samples, and positive identification of L. zosterae cells in histological samples qualitatively indicated the presence of the pathogen within plant cells (Supporting Information Table S9). Together, the qPCR and histology indicated that lesions visually identified as eelgrass wasting disease were signs of infection by L. zosterae , supported by prior studies that confirmed L. zosterae infection in field‐identified lesion tissue at several of our study sites in WA and OR (Groner et al 2016; Yoshioka et al 2019).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Positive amplification of L. zosterae DNA from diseased tissue samples confirmed the presence of this pathogen in lesion tissue samples, and positive identification of L. zosterae cells in histological samples qualitatively indicated the presence of the pathogen within plant cells (Supporting Information Table S9). Together, the qPCR and histology indicated that lesions visually identified as eelgrass wasting disease were signs of infection by L. zosterae , supported by prior studies that confirmed L. zosterae infection in field‐identified lesion tissue at several of our study sites in WA and OR (Groner et al 2016; Yoshioka et al 2019).…”
Section: Resultssupporting
confidence: 84%
“…1) (Sullivan et al 2013, 2018). The presence of L. zosterae can be further verified with microscopy, culturing, and/or quantitative PCR (qPCR) (Bockelmann et al 2013; Groner et al 2016; Yoshioka et al 2019). However, identification and quantification of lesion area are laborious and rely on specialized expertise, complicating surveillance at scales relevant to management and limiting our ability to forecast outbreaks or develop mitigation measures.…”
Section: Figmentioning
confidence: 99%
“…S16), our results imply that even detritivorous amphipods may rely on decomposing diatoms for maintaining consistent nutrition along the disturbance gradient. Second, amphipods themselves (Pilecky et al 2021) or symbionts (Yoshioka et al 2019) may upgrade fatty acids by investing energy to convert C18 fatty acids to C20 fatty acids. Third, amphipods may migrate to deep littoral zones (e.g., 10–100 m), where diatoms may be more abundant, but then return to shallow littoral areas where breeding occurs (e.g., < 10 m; Takhteev and Didorenko 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic substrate samples were collected in June 2021 from the same three habitats with orange crusts at Waikoloa (WAI) and Kapalaoa Bay (AB, AC) described above and from two green mat habitats at Hualalai Resort (HA and Ho 0 onanea because HB and HC were exposed at low tide at time of sampling). Single samples from each habitat (except two from opposite sides of Ho 0 onanea, which is a large pond) were processed following methods of Taipale et al (2016) and Yoshioka et al (2019) (see Supplementary Appendix S1).…”
Section: Fatty Acids In Orange Crusts Vs Green Matsmentioning
confidence: 99%